2003
DOI: 10.1089/153056203772744653
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of In-Person Examination and Video Otoscope Imaging for Tympanostomy Tube Follow-Up

Abstract: The objective of this study was to determine if video otoscope still images (640 x 480 pixel resolution) of the tympanic membrane following surgical placement of tympanostomy tubes are comparable to an in-person microscopic examination. Forty patients having undergone tympanostomy tube placement in both ears were independently examined in-person by two otolaryngologists and imaged using a video otoscope and telemedicine software package. The two physicians later reviewed images at 6 and 12 weeks. Physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
88
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 44 publications
11
88
0
2
Order By: Relevance
“…typically apparent through use of interactive binocular microscope examination 12 or pneumatic otoscopy. Typically, in field face-toface otologic assessment, medical, demographic, and social history, in conjunction with techniques such as tympanometry and pure tone audiometry, would be used in addition to video-otoscopy or conventional otoscopy.…”
Section: Video-otoscopy With Telehealth Facilitatormentioning
confidence: 99%
See 4 more Smart Citations
“…typically apparent through use of interactive binocular microscope examination 12 or pneumatic otoscopy. Typically, in field face-toface otologic assessment, medical, demographic, and social history, in conjunction with techniques such as tympanometry and pure tone audiometry, would be used in addition to video-otoscopy or conventional otoscopy.…”
Section: Video-otoscopy With Telehealth Facilitatormentioning
confidence: 99%
“…8,9 Previous studies concluded that video-otoscopic images are equivalent in quality to face-to-face otoscopy. 6,8,[10][11][12] A comparison of four video-otoscopes found that three of the four systems yielded images rated as adequate or better for at least 80% of the images. 8 Previous studies reported 75-82% of video-otoscopic images were judged to be adequate, good, very good, or excellent in quality.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations